(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2019)
Climate change has undoubtedly brought with it many seemingly intractable challenges and is already having significant impacts in Nigeria, and these impacts are expected to increase in the future. Rural dwellers environmental behaviour is not all that positive, because the language used in disseminating environmental issues, is mostly English and not the indigenous language. Information disseminated in English Language in most cases is not easily comprehended, because most of the rural dwellers are not literate in it. The instrument used is a self-constructed test. The study adopted the quasi experimental method. Purposeful sample was used to select two groups, with twenty people in each group. The two groups were taught the causes and effects of climate change, one group was taught using English Language and the other group using Yoruba. A test was administered to each group to determine their level of comprehension. Data were analysed using mean and standard deviation. Yoruba group are more in-depth in their knowledge of climate change than English group. The use of mother tongue is germane in the dissemination of information regarding environmental sustainability, however climate change messages will be most effective if there is mix of English Language and Yoruba Language as there is no segment of the society that will be left out.